The wedding veil [large type] - Harvey, Kristy Woodson (Center Point Large Print, 2022)
"Four women. One family heirloom. A secret connection that will change their lives...and history as they know it. Present Day: Julia Baxter's wedding veil, bequeathed to her great-grandmother by a mysterious woman on a train in the 1930s, has passed through generations of her family as a symbol of a happy marriage. But on the morning of her wedding day, something tells Julia that even the veil's good luck isn't enough to make her marriage last forever. Overwhelmed and panicked, she escapes to the Virgin Islands to clear her head. Meanwhile, her grandmother Babs is also feeling shaken. Still grieving the death of her beloved husband, she decides to move out of the house they once shared and into a retirement community. Though she hopes it's a new beginning, she does not expect to run into an old flame, dredging up the same complicated emotions she felt a lifetime ago. 1914: Socialite Edith Vanderbilt is struggling to manage the luxurious Biltmore Estate after the untimely death of her cherished husband. Edith is determined to uphold the Vanderbilt legacy, and prepare her free-spirited daughter Cornelia to inherit it...in spite of her family's deteriorating financial situation. But Cornelia has dreams of her own. As she explores more of the rapidly changing world around her, she's torn between upholding tradition and pursuing the exciting future that lies beyond Biltmore's gilded gates."--